Blockchain adoption in food supply chains: a review and implementation framework. Issue 6 (26th April 2023) - Vu, Nam; Ghadge, Abhijeet; Bourlakis, Michael
Abstract: Blockchain technology has received significant attention from the food industry; however, due to the scarcity of successful Blockchain projects and sector-specific studies, a step-by-step approach for implementing Blockchain in food supply chains (FSCs) is still missing. A systematic literature review of 69 high-quality, peer-reviewed articles is utilized to capture Blockchain adoption drivers and barriers, applications, and implementation stages within FSCs. Current Blockchain issues such as scalability, regulations, privacy, and incentivization are identified as future research opportunities. Following innovation adoption theory, a three-stage conceptual framework for Blockchain implementation in FSCs is developed. The proposed framework is novel and is expected to benefit food chain managers in establishing the suitability of Blockchain for their organization and/or wider supply network. Identified influential factors, case examples, and implementation stages are expected to guide practitioners in developing a roadmap for adopting Blockchain in the food industry.